CSC575 - Software Project Management / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2022)
This course introduces project management as a discipline/profession. It focuses on theories related to project definition, project scope, project tools and implementation. Key aspects include professional development, organization design and project structure, communication, managing change and performance measurement (time, cost and quality) are covered. This course also introduces key concepts in better understanding the role of innovation and technology and its efficient management, to build and maintain a competitive edge in business.Innovation and technology management links software engineering, science and management principles to identify, choose and implement the most effective means of attaining compatibility between an organization and its competitive, economic and social environment. This course also introduces the students to software project management tools that can effectively track and manage the project information. Overall, this course synthesizes a comprehensive range of software project knowledge into a management-oriented structure in order to benefit the students’ future professional career.